Pengaruh Pembelajaran Berbasis Proyek Terhadap Hasil Belajar dan Kemampuan Berpikir Kritis Peserta Didik Kelas V Sekolah Dasar Materi Unsur-Unsur Intrinsik Cerita - Nanik Kurnia Sugiarti; Tatag Yuli Eko Siswono; Ucu Rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of the application of the Project Based Learning (PjBL) model on the learning outcomes and critical thinking skills of grade V elementary school students on the intrinsic elements of the story. The study used a pseudo-experiment method with a fixed group design and involved 90 students of SD Khadijah 3 Surabaya who were proportionally divided into experimental and control groups. The research instruments include multiple-choice tests, essays, documentation, and questionnaires. The results showed that the application of PjBL could significantly improve students' critical thinking skills, with the N-gain score of the experimental group reaching 57.6% (the category of quite effective), compared to the control group of 15.46%. However, the effectiveness of PjBL on academic learning outcomes based on conventional tests is still low, with the average N-gain of the experimental group of 12.49% and the control group of 18.58%. Thus, PjBL is recommended to improve students' critical thinking skills, but it is still necessary to develop assessment strategies so that academic learning outcomes can also be optimal.